Tuning sulfur fixation via conditioner–oxygen synergy during oxidative pyrolysis of sewage sludge under smouldering conditions - Shan Cheng; Linxi Guo; Hong Tian; Dangzhen Lv; Junjie Huang; Jiaxin Yu (Fuel, 2026)

Effects of Dietary Supplementation with Selenium-Enriched Lactobacillus plantarum on Growth, Hepatic Antioxidant Capacity, and Intestinal Microbiota of Largemouth Bass (Micropterus salmoides) - Chengxu Ruan; Junhao Tang; Xiufang Liu; Junwei Chen; Linxi Cheng; Xucong Lv (Fishes, 2026)
This study compared the effects of dietary Lactobacillus plantarum (Lpl) and selenium-enriched L. plantarum (Lpl_se) on the growth, hepatic antioxidant capacity, and intestinal microbiota of juvenile largemouth bass (initial weight 12.50 ± 0.81 g). Following a 58-day trial in an indoor rearing system, data were analyzed using one-way ANOVA followed by Tukey’s HSD test. Results showed that both Lpl and Lpl_se significantly improved growth versus the control (Weight Gain Rate: 379.82% and 387.18% vs. 326.56%; p

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Insight in the role of organic nitrogen compounds in organic sulfur release during sewage sludge pyrolysis: A experimental and theoretical study - Shan Cheng; Kehui Yao; Linxi Guo; Wen Chen; Zihui Xu; Hong Tian (Fuel, 2026)

Cadmium and Benzo[a]pyrene Co-exposure Synergistically Induces Apoptosis in Bronchial Epithelium: Mechanistic Insights and Predictive Risk Modeling for Indoor Dust - Junbo Liu; Linxi Yang; Jixiang Chen; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Biological Trace Element Research, 2025)

High-temperature calcination modified red clay as an efficient adsorbent for phosphate removal from water - Kanglong Cheng; Qin You; Linxi Zou; Yu Zhang; Peng Wang; Wen Zhang (Environmental Research, 2025)

Development of a Golgi-targeted superoxide anion fluorescent probe for elucidating protein GOLPH3 function in myocardial ischemia-reperfusion injury - Ao Li; Yalan Liu; Labapuchi; Zhe Chen; Songjiao Li; Rongbin Zhong; Dan Cheng; Linxi Chen; Longwei He (Analytica Chimica Acta, 2023)

Total photosynthetic biomass record between 9400 and 2200 BP and its link to temperature changes at a High Arctic site near Ny-Ålesund, Svalbard - Zhongkang Yang; Jianjun Wang; Linxi Yuan; Wenhan Cheng; Yuhong Wang; Zhouqing Xie; Liguang Sun (Polar Biology, 2019)